Penyusutan dan Nilai Guna Arsip di Unit Kearsipan Dinas Prasarana Jalan, Tata Ruang dan Pemukiman Provinsi Sumatera Barat - Fitri, Iftah Annisa; Marlini, Marlini (Ilmu Informasi Perpustakaan dan Kearsipan, 2013)
The purpose of this paper is: (1) describe how the process of archives in archival unit depreciation Road Infrastructure Agency, Spatial Planning and Housing of West Sumatra province, (2) describe how the depreciation value of archives in archival unit for Road Infrastructure Agency, Spatial Planning and Settlement West Sumatra province, (3) to find out what are the constraints faced by archival unit Spatial Agency Road Infrastructure and Settlement in the province of West Sumatra and the archives shrinkage problem solving. Research done by: (1) observation, the observation in the archival unit, observations recorded are as where the condition of the room archives, archives conditions, completeness of facilities and materials to shrink the file, (2) interviews with archivists. The result is, the stages depreciation and depreciation records to archives in archival unit Agency Road Infrastructure, Spatial Planning and Housing of West Sumatra province as a whole is running properly with depreciation criteria for a pretty good value too. Constraints faced is the lack of skilled labor, and frequent staff off and leave work at noon, making it difficult to perform depreciation archives with little power, also the lack of attention from head office so that the equipment and supplies needed to shrink the archives are often less satisfied. Keywords: archive; use value; depreciation